Leveraging Digital Technology to Strengthen Adult Education and Engagement in Islamic Study Group (Majlis Ta’lim) - Silvi Ratnawulan; Nurhayati, Sri; Taufikin; Fatima Zahra Lotfi; Olugbade, Damola (Journal of Education Research, 2025)
This study investigates the impact of the digital paradigm on community building, educational experiences, and the sense of belonging in Islamic education through a case study of Majelis Ta'lim Fitya Center in New South Wales, Australia. The hybrid learning approach enhances accessibility and flexibility, while digital platforms such as WhatsApp strengthen interaction and interpersonal relationships. The findings reveal that digital technology supports inclusivity in community-based Islamic education. However, challenges such as the lack of formal feedback mechanisms and content scalability remain significant concerns. The key implications of this study highlight the importance of integrating feedback mechanisms into Islamic education policies and developing sustainable digital programs to foster more inclusive communities.